1990
DOI: 10.1073/pnas.87.24.9577
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of interleukin 2 and various effector cell populations in adoptive immunotherapy of 9L rat gliosarcoma: allogeneic cytotoxic T lymphocytes prevent tumor take.

Abstract: Recombinant interleukin 2 (rIL-2) and various effector cell populations were used for adoptive immunotherapy in the Fischer strain 9L rat gliosarcoma model. The in vivo cytotoxicities of nonspecifically activated lymphocytes and specifically activated cytotoxic T lymphocytes (CTLs) were assessed in a modified in vivo neutralization (Winn) assay.Effector cells (106) those who received syngeneic unstimulated T lymphocytes and rIL-2. For a set of animals given the same inoculum of 9L tumor, significantly improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Glioma cells express major histocompatibility complex class I and class II molecules (3), as well as tumor-associated antigens that have been demonstrated to stimulate anti-tumor immune responses and thus are good tumor vaccine candidates (4,5). However, several studies have demonstrated the secretion of an immunosuppressive factor by glioma cells that was subsequently identified as transforming growth factor P (TGF-/3) (6-9).…”
Section: %) or 9l Cells Transduced With An Interleukin 2 Retroviralmentioning
confidence: 99%
“…Glioma cells express major histocompatibility complex class I and class II molecules (3), as well as tumor-associated antigens that have been demonstrated to stimulate anti-tumor immune responses and thus are good tumor vaccine candidates (4,5). However, several studies have demonstrated the secretion of an immunosuppressive factor by glioma cells that was subsequently identified as transforming growth factor P (TGF-/3) (6-9).…”
Section: %) or 9l Cells Transduced With An Interleukin 2 Retroviralmentioning
confidence: 99%
“…We have reported on the in vivo response of Interleukin-2 with various effector cell preparations activated to kill 9L gliosarcoma when locally adoptively transferred in the rat model system [3]. Nonspecifically-activated syngeneic L A K cells, adherent or nonadherent, were capable of extending survival but did not offer cures.…”
Section: Discussionmentioning
confidence: 98%
“…Our laboratory has reported on the in vitro and in vivo efficacy of human recombinant Interleukin-2 (rIL-2) with various preparations of cells which have been nonspecifically activatedto kill tumor in the rat 9L tumor model [3,4]. We have also reported the long-term follow-up of patients with recurrent malignant brain tumors treated by the Denver Brain Tumor Research Group with nonspecifically activated killer cells in conjunction with rIL-2 [2].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…An adaptive immune response implies antigen recognition (Prasad et al, 2004). A variety of immunologically based strategies, including passive immunization and adoptive cellular immunotherapy (Fujimiya et al, 1999;Inoue et al, 1996;Kruse et al, 1990;Merchant et al, 1997;Plautz et al, 1997;Plautz et al, 1998) local and systemic delivery of biological response modifiers (Dranoff et al, 1993;Färkkilä et al, 1994;Jean et al, 1998;Jean et al, 2004;Lichtor et al, 1995;Ohno et al, 2009;Thompson et al, 1996;Yu et al; and vaccination with parental and genetically modified tumor cells (Dranoff et al, 1993;Jean et al, 1998;Lichtor et al, 1995;Thompson et al, 1996;Ohno et al, 2009;Yu et al; have been attempted.…”
Section: Immunotherapymentioning
confidence: 99%